(untitled) (INTERNATIONAL SCIENCE REVIEWS. SOCIAL SCIENCES SERIES, 2024)
Central Asia (Kazakhstan, Uzbekistan, Tajikistan, Kyrgyzstan and Turkmenistan) is the largest post - Soviet bloc after Russia. It connects the western and eastern parts of Eurasia and the gap between the developed North and the developing South. In addition, Central Asia is one of the richest regions in the world in terms of mineral reserves. Its spatial location and resource richness make this sub-region an important part of a large political game.